Spin dynamics and field-induced magnetic phase transition in the honeycomb Kitaev magnet alpha-Li2IrO3 - Choi, S; Singleton, J; Lancaster, T; Blundell, S; Coldea, R (University of Oxford, 2019)
The deposited package contains magnetic susceptibility, muon spin relaxation, powder inelastic neutron scattering and pulsed-field magnetization data of the honeycomb Kitaev magnet alpha-Li2IrO3. The readme file inside the .zip archive contains detailed information about the individual file formats in the data archive.